Restored teeth can be used as samples for genotyping?. (December 2015) - Corte-Real, A.; Silva, D.N.; Vieira, D.N.; Corte-Real, F.; Anjos, M.J.
Abstract: The aim of this study is to warn that such samples should not be overlooked for a successful genotyping. Six restored dental pieces were randomly selected from extreme forensic situations. For each tooth two portions have been selected: the dentin of adjacent portions of the restoration area (DS) and the remaining root dentin (DR). DNA extraction was executed using the PrepFiler ​TM BTA kit according to the manufacturer's instructions and its quantification was realized with the Quantifiler ​TM Duo kit (both from Applied Biosystems). DS quantification values were comparatively higher than those of DR portion.These results may be related to a tertiary dentin formation, restorative and disorganized. The use of a sample with dentin tissue adjacent to a restoration area, covering the entire portion up to the pulp cavity, proved to be a good sample for genetic analysis, optimizing the quality of the sample volume.